Knockdown of GPR137, G Protein‐coupled receptor 137, Inhibits the Proliferation and Migration of Human Prostate Cancer Cells. (17th January 2016) - Ren, Jizhong; Pan, Xiuwu; Li, Lin; Huang, Yi; Huang, Hai; Gao, Yi; Xu, Hong; Qu, Fajun; Chen, Lu; Wang, Linhui; Hong, Yi; Cui, Xingang; et al.
Abstract : GPR137 belongs to the G protein‐coupled receptor family involving the regulation of transmembrane signal transduction that launches pivotal cellular functions. However, its function in prostate cancer (PCa) has been rarely reported. It was found in this study that GPR137 was upregulated in PCa tissues as compared with that in paracancerous tissues. To see whether GPR137 could serve as a potential therapeutic target for PCa, GPR137 was knocked down to verify its biological function in PCa cells. Lentivirus‐introduced short hairpin RNA (shRNA) was designed to silence GPR137 gene. It was found that silencing of GPR137 gene suppressed the proliferation and colony formation of PCa cell lines PC‐3 and DU145. Further study indicated that growth inhibition by GPR137 knockdown was associated with cell cycle arrest at G0/G1 phase. Furthermore, silencing of GPR137 repressed the invasion and migration abilities of PC‐3 cells via downregulating slug and snail and upregulating E‐cadherin. Collectively, these findings imply that GPR137 plays an important role in the occurrence and progression of PCa and may prove to be a potential therapeutic target for the treatment of advanced PCa. Abstract : GPR137 belongs to the G protein‐coupled receptor family involving regulation of important cellular functions. Silencing of GPR137 gene suppressed the proliferation and colony formation of prostate cancer cell lines PC‐3 and DU145 via G0/G1 cell cycle arrest. Furthermore, silencing of GPR137 repressed cell migration ability of PC‐3 and DU145 by downregulating snail1 and slug and up‐regulating E‐cadherin. So GPR137 plays an important role in the occurrence and progression of prostate cancer and acts as a potential therapeutic target for advanced PCa.